Non-apoptotic activity of the mitochondrial protein SMAC/Diablo in lung cancer: Novel target to disrupt survival, inflammation, and immunosuppression - Pandey, Swaroop Kumar; Shteinfer-Kuzmine, Anna; Chalifa-Caspi, Vered; Shoshan-Barmatz, Varda (Frontiers in Oncology, 2022)
Mitochondrial SMAC/Diablo induces apoptosis by binding the inhibitor of apoptosis proteins (IAPs), thereby activating caspases and, subsequently, apoptosis. Previously, we found that despite its pro-apoptotic activity, SMAC/Diablo is overexpressed in cancer, and demonstrated that in cancer it possesses new essential and non-apoptotic functions that are associated with regulating phospholipid synthesis including modulating mitochondrial phosphatidylserine decarboxylase activity. Here, we demonstrate additional functions for SMAC/Diablo associated with inflammation and immunity. CRISPR/Cas9 SMAC/Diablo-depleted A549 lung cancer cells displayed inhibited cell proliferation and migration. Proteomics analysis of these cells revealed altered expression of proteins associated with lipids synthesis and signaling, vesicular transport and trafficking, metabolism, epigenetics, the extracellular matrix, cell signaling, and neutrophil-mediated immunity. SMAC-KO A549 cell- showed inhibited tumor growth and proliferation and activated apoptosis. The small SMAC-depleted ”tumor” showed a morphology of alveoli-like structures, reversed epithelial-mesenchymal transition, and altered tumor microenvironment. The SMAC-lacking tumor showed reduced expression of inflammation-related proteins such as NF-kB and TNF- and of the PD-L1, associated with immune system suppression. These results suggest that SMAC is involved in multiple processes that are essential for tumor growth and progression. Thus, targeting SMAC’s non-canonical function is a potential strategy to treat cancer.